Pengelolaan Hubungan Antara Dokter Dan Pasien Dalam Konteks Komunikasi Terapeutik - Kevin Purba; Turnomo Rahardjo (Interaksi Online, 2020)
Basically, the therapeutic relationship between doctor and patient must be managed in such a way as to provide good health outcomes to patients. To make it happen, good communication competence is needed by doctors besides only relying on their knowledge to treat. This research is motivated by the existence of communication problems found in the scope of health, such as cases of malpractice due to a lack of explanation for the provision of health information by doctors, lack of humanist character of doctors to unidirectional communication models by doctors which ultimately lead to bad perceptions regarding communication services provided by doctors. doctors in Indonesia. This study aims to understand how the patterns of interaction in the therapeutic relationship between doctors and patients and to understand what are the obstacles that often occur in the therapeutic relationship between doctors and patients. This research refers to an interpretive paradigm with a phenomenological approach. The theory used in this research is the (Expectacy Violation Theory / EVT) theory by Judee Burgoon and the theory of Relational Dialetics by Lexlie Baxter and Barbara Montgomery. The data collection technique used in this study was indepth interviews with research subjects doctors and patients. The results of this study revealed that there are four stages in the therapeutic tangle between doctor and patient that is, pre-interaction, orientation, work(working)and termination, where the stages of working is at the core of the fabric of the therapeutic. The relationship between doctors and patients is created because of the attraction so that the pattern of therapeutic interactions in this study refers to the principle of complementarity. In this study, there are 5 main aspects that are the key to how the relationship between doctor and patient can be managed properly, namely empathy, trust, openness or openness, unconditional positive attention and also equality. Meanwhile, the obstacles to the therapeutic relationship felt by doctors and patients in this study were in certain contexts and situations, such as when discussing complaints and during the doctor's visit.